Radiotherapy for a benign cause of cauda equina compression in a known case of breast carcinoma. (19th June 2013) - Bhalla, Neeraj; Husband, David J; Pillay, Robin; Thorp, Nicki
Abstract : A woman underwent breast conservation surgery and axillary clearance for T1N1M0 breast carcinoma, followed by adjuvant chemotherapy, radiotherapy and hormone therapy. At 3-year follow-up she presented with lumbar back pain and developed bilateral lower limb weakness. MRI spine demonstrated an expansile lesion at L1 causing cauda equina compression. The mass, unusually, was centred on the spinous process; metastases typically involve pedicles. The patient underwent surgical decompression with complete resolution of neurological signs. Histology revealed Masson tumour (intravascular papillary endothelial hyperplasia), a benign vascular lesion. Pain recurrence 9 months later prompted imaging demonstrating recurrent mass. Preoperative embolisation and re-excision was undertaken for recurrent Masson tumour. Recurrence of these lesions is rare and it was felt residual disease was likely. Radiotherapy has been used in isolated cases; therefore, she was treated with adjuvant radiotherapy, the first reported case of radiation in management of extracranial Masson tumour, and remains well 3 years later.